Jesse Owens : fastest man alive - Weatherford, Carole Boston, 1956-; Velasquez, Eric. (New York : Walker & Co. : Distributed to the trade by Holtzbrinck Pub., 2007)
A simple biography of one of the most inspirational athletes in history.
Includes bibliographical references.
Keywords: Owens, Jesse, -- 1913-1980 -- Juvenile literature; Owens, Jesse, -- 1913-1980.; African American athletes -- Biography -- Juvenile literature; African American track and field athletes -- Biography; Athletes -- United States -- Biography -- Juvenile literature; Track and field athletes -- United States -- Biography -- Juvenile literature; African American athletes -- Biography; African Americans -- Biography; Athletes -- United States -- Biography; Track and field athletes -- United States -- Biography